Methodological Guidelines in Philologists’ Professional Training - Ikonnikova, Maryna (Pedagogical Discourse, 2016)
In the article the author has actualized the need to improve philologists’ professional training taking into account different concepts, theories, ideas, methodological approaches and principles. Methodological guidelines in the research of the problem raised which form the basis for further theoretical study of the peculiarities of philologists’ professional training and justification of conceptual foundations needed for the development of philologists’ professional training system have been defined. The analysis of methodological approaches to philologists’ professional training (axiological, synergistic, culturological, anthropocentric, competency-based, systemic, activity-based and personality-oriented) has been conducted. Basic principles of these approaches and the expediency of their use in professional training of philologists have been characterized. Special attention has been paid to philosophy of anthropocentrism and cultural centrism as new guidelines in modern philosophy of education. It has been noted that philosophy of anthropocentrism and cultural centrism focuses on the development of human self-consciousness, cultural correspondence, cultural identity, understanding of human nature, comprehending of human originality and therefore stipulates for human development. The need to use a synergetic paradigm, that ensures philologists’ autonomic development through specifically configurable influences: by a teacher – creation and implementation of optimal pedagogical conditions, by students – participation in modeled professionally oriented situations, has been revealed. In particular, culturological and competency-based approaches have been emphasized as they orient professional training of philologists to the development of their spiritual culture and social responsibility, professional competences, creativity, critical thinking, communication skills. The socio-pedagogical portrait of a modern philologist as a tolerant, cultural and linguistic personality who comprehends his/her national roots, respects the values of other cultures, can inspire via «live», emotional, passionate words from both native and foreign languages, has a high level of scientific culture and aesthetic taste, has been decribed. The importance of integration of the above mentioned approaches that will stipulate for improving professional training of philologists, combining the objectives, content, structure, stages, forms, methods of teaching and learning organization, providing a systematic vision of the harmonious development of a philologist’s cultural and linguistic personality, has been accentuated. Key words: philologists, methodological approaches, anthropocentrism, cultural and linguistic personality, axiological orientations, professional competences.